2012
DOI: 10.1098/rspb.2012.1229
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic intraspecific differences in migratory routes, stopover sites and wintering areas, revealed using light-level geolocators

Abstract: Migratory divides are contact zones between breeding populations that use divergent migratory routes and have been described in a variety of species. These divides are of major importance to evolution, ecology and conservation but have been identified using limited band recovery data and/or indirect methods. Data from band recoveries and mitochondrial haplotypes suggested that inland and coastal Swainson's thrushes (Catharus ustulatus) form a migratory divide in western North America. We attached light-level g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
201
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(215 citation statements)
references
References 41 publications
14
201
0
Order By: Relevance
“…Using an array of automated radio-telemetry receiving stations, we confirmed long-held predictions that blackpolls exhibit prolonged stopover in the GOM during fall migration (Nisbet et al 1963, 1995, Nisbet 1970 Delmore et al 2012). Blackpolls and vireos also exhibited lower movement rates throughout the study area than typically reported for long-distance migrants from banding (60 km day À1 ; Ellegren 1993) or geolocator studies (68-473 km day À1 ; Fraser et al 2013), which suggests that birds were predominantly stopped while in our study area.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Using an array of automated radio-telemetry receiving stations, we confirmed long-held predictions that blackpolls exhibit prolonged stopover in the GOM during fall migration (Nisbet et al 1963, 1995, Nisbet 1970 Delmore et al 2012). Blackpolls and vireos also exhibited lower movement rates throughout the study area than typically reported for long-distance migrants from banding (60 km day À1 ; Ellegren 1993) or geolocator studies (68-473 km day À1 ; Fraser et al 2013), which suggests that birds were predominantly stopped while in our study area.…”
Section: Discussionsupporting
confidence: 49%
“…Although staging activity is typically attributed to shorebirds and waterfowl (Dunne et al 1982, Newton 2008, numerous geolocator studies have recently reported passerines making stops ranging from 8 to 36 days (Heckscher et al 2011,Åkesson et al 2012, Delmore et al 2012, Tøttrup et al 2012, Callo et al 2013, Fraser et al 2013, Jahn et al 2013, Kristensen et al 2013, Renfrew et al 2013, Wolfe and Johnson 2015, Van Loon et al 2017 that are analogous in length to staging events. Stops of .7 days surpass the amount of time theoretically expected for migratory refueling under optimality models (Alerstam 1991) and have been classified as ''prolonged stopover''-a behavior distinct from typical songbird stopover (McKinnon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Density estimates, considered in combination with other factors, may therefore be one of the most cost-effective and efficient means of assessing habitat quality. This does not preclude, however, the initial establishment of evidence for multiday stopovers (Delmore et al 2012) and active energy deposition (Bayly et al 2013), because high densities can occur at sites rarely used for fueling, e.g., sites used in emergencies, often referred to as "fire escapes" (Mehlman et al 2005). Our finding that densities were not uniform but varied between transects, presumably because of flocking behavior or clumped resources, e.g., fruiting trees, emphasizes the importance of surveying a representative area of the habitats of interest (Thomas et al 2010).…”
Section: Indicators Of Habitat Qualitymentioning
confidence: 99%